Characterization of potent anticholinesterase plant oil based microemulsion - Chaiyana W. (2014)
In the present study, essential oils of three edible Thai plants, Cymbopogon citratus (Gramineae), Citrus hystrix (Rutaceae) and Zingiber cassumunar (Zingiberaceae) were comparatively tested for acetylcholinesterase (AChE) and butyrylcholinesterase (BChE) inhibitory activities using Ellman's colorimetric method. C. citratus oil exhibited the highest activity with IC 50 values of 0.34±0.07μl/ml and 2.14±0.18μl/ml against BChE and AChE activity, respectively. It was further investigated whether microemulsions of this oil could be obtained. The effects of type of surfactant and co-surfactant as well as pH and ionic strength on the phase behavior of the oil/water system were investigated. Brij 97, Triton X-114, Tween 20 and Tween 85 were employed as surfactant whereas ethanol and hexanol were used as cosurfactants. The size analysis, electrical conductivity measurements and cholinesterase inhibition assays were done in selected microemulsion. The results revealed that the type and concentration of surfactant and co-surfactant exhibited a distinct influence on the C. citratus oil microemulsions. Moreover, the inhibitory activities of the microemulsion formulation were remarkable. © 2010 Elsevier B.V.